Hydrodynamics across seagrass meadows and its impacts on Indonesian coastal ecosystems: A review - Risandi, Johan; Rifai, Husen; Lukman, Kevin M.; Sondak, Calvyn F. A.; Hernawan, Udhi E.; Quevedo, Jay Mar D.; Hidayat, Rahman; Ambo-Rappe, Rohani; Lanuru, Mahatma; McKenzie, Len; Kohsaka, Ryo; Nadaoka, Kazuo (Frontiers in Earth Science, 2023)
Seagrass canopies are important components of the world’s coastal environments providing critical ecological services. Nearshore hydrodynamics, i.e., waves and currents, are essential in controlling the ecological processes across coastal environments. Seagrass meadows can impose more complex hydrodynamics processes by attenuating sea-swell waves and decreasing the impact of nearshore mean water level rise due to wave setup and Infragravity (IG) waves. Consequently, the seagrasses dissipate waves and reduce flows allowing sediments to settle and accrete the shorelines. However, despite their significant roles, knowledge of hydrodynamics in the Indonesian seagrass ecosystems is relatively limited compared to other coastal ecosystems such as sandy beaches, mangroves, and coral reefs. This review highlights the dynamics of waves and currents, and their interaction with sediment transport and ecological processes, including biogeochemical and dispersal processes on the seagrass ecosystem contributing to the existing seagrass research in Indonesia. The associated literature is collected from scientific databases such as Scopus and Google Scholar that range between 1965 and 2021. The result showed that most of the research on hydrodynamic in seagrass ecosystems was carried out in temperate zones. Until recently, there have been limited publications discussing the interaction between the Indonesian (tropical) seagrass ecosystem and hydrodynamics parameters, even though the region has abundant seagrass species. Moreover, Indonesia is strongly influenced by various atmospheric-oceanic forcing, including the Asian monsoon affecting the dynamic of the coastal area with seagrass ecosystems. At a canopy scale, the correlation between the nearshore (tropical) hydrodynamics and ecological processes in the system is yet to be explored. Considering the potential benefit of seagrasses to coastal ecosystems, developing future research in hydrodynamics across the ecosystem is critical to overcoming the knowledge gaps in Indonesia. The knowledge gained could support the Indonesian seagrass ecosystem services and their resilience to potential hazards and climate change.